SYMBOLIC MEANING OF THE WHITE BIRD DANCE IN PUTRI SAK AYU STUDIO, MUSI BANYUASIN REGENCY - Saptaji Saptaji (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the symbolic meaning of the Burung Putih Dance within the cultural context of the Musi Banyuasin community. The research employs a qualitative descriptive method with a case study approach conducted at Sanggar Putri Sak Ayu, Musi Banyuasin Regency. Data were collected through observation, interviews with instructors, dancers, and art observers, as well as documentation in the form of photos and performance videos. Data analysis refers to the theory of symbolism in dance. The results show that the symbolic meanings of the Burung Putih Dance are reflected in each movement sequence. The wing-flapping movement symbolizes peace and freedom, the right and left kecubung movement represents the act of driving away pests as a symbol of the relationship between humans and nature in agrarian life, and the bird formation movement reflects togetherness and cooperation. These meanings indicate that the dance movements are not only representational but also contain philosophical values such as harmony, balance, and mutual cooperation, which are integral to the life of the Musi Banyuasin community. The findings affirm that the Burung Putih Dance functions not only as an aesthetic performance but also as a medium for conveying cultural values and local wisdom.